REVISION OF PLATHYMENIA (LEGUMINOSAE–MIMOSOIDEAE) - WARWICK, M. C.; LEWIS, G. P. (Edinburgh Journal of Botany, 2003)
Plathymenia (Leguminosae–Mimosoideae) has been variously regarded as comprising one to three species and one variety. The genus is here considered to be monospecific, containing only Plathymenia reticulata. This is in agreement with the conclusion of Ducke in 1925. A full description is given of P. reticulata in its emended sense, with notes on ecology, uses, vernacular names and a list of herbarium specimens examined.
Keywords: Cerrado; Fabaceae; lectotypification; monospecific; neotropics; seasonally dry tropical forest; vinhático